Studies on antidiabetic herbal formulations available in the herbal stores of Karachi, Pakistan - Erum Shah (GarVal Editorial Ltda., 2022)
Context: Diabetes mellitus is a condition, which is characterized by persistent hyperglycemia, abnormal functioning of insulin and difficulty in the metabolism of carbohydrates, fats and proteins. Antidiabetic medicines of herbal origin are widely consumed in Pakistan. Therefore, there was a need to generate data on antidiabetic herbal formulations manufactured and marketed in Pakistan. Aims: To develop a list of Pakistani manufactured antidiabetic herbal products and the most common herbal ingredients found in them. Methods: Antidiabetic herbal formulations were collected from the renowned herbal stores of Karachi, Pakistan, and their ingredients were checked. The most common herbal ingredients found in them were determined, and the possible constituents responsible for the antidiabetic action of these herbs were discovered. Results: A total of 15 herbal antidiabetic products were collected from the herbal stores. The most common herbs found in them include Syzygium cumini, Gymnemma sylvestre, Aloe vera, Nigella sativa, Acacia nilotica, Commiphora myrrha, Portulaca oleracea, Punica granatum, Rhus coriaria, Coriandrum sativum, Trigonella foenum-graecum, Bambusa bambos, Holarrhena antidysenterica, Swertia changii, Curcuma longa and Rumex vesicarius. The constituents responsible for antidiabetic activity include alkaloids, polysaccharides, glycosides, secoiridoid, phenolic acids, flavonoids, terpenoids, saponins and volatile oil. Conclusions: The herbs incorporated in these formulations have proven antidiabetic effects; therefore, these formulations can produce significant results in the management of diabetes. More research on each of these formulations is needed to confirm the potency of all these herbal products.